Strategi Meningkatkan Akuntabilitas dan Transparansi Pengelolaan Kas Badan Layanan Umum - Isti’anah Isti’anah; Eko Setiyo Utomo (Public Inspiration : Jurnal Administrasi Publik, 2024)
The growth in the number of BLU shows an increasing trend until early 2022. Along with this increase in number, the contribution of BLU to non-tax state revenue (PNBP) also shows a positive upward trend. Almost every year state revenue from BLU continues to increase. However, the recording of this income to the state treasury is only done once every three months, so the Minister of Finance as BUN cannot know in real time. This study aims to: assess the transparency of BLU's financial management, provide alternative proposals for managing BLU accounts, and develop existing research results. Researchers explore the object of research using qualitative methods with more focus on policy analysis. In policy research studied is the policy that is being implemented. The research objects are four BLU work units in Jambi. The steps in this research include identifying the main issues, then formulating the problem, followed by developing an action plan for policy implementation and the last is conducting monitoring and evaluation. The results of this study indicate that there is a difference between the data in SPAN and the work unit’s report. The work unit reports once every three months so that the error is only discovered when they carry out the SP3B validation. Reporting delays cause problems if there are logging errors. Repairs must be carried out with a mechanism that is quite complicated and will require considerable power and effort. To overcome the current conditions, it is necessary to improve policies so that the revenue managed by BLU can be monitored at any time by BUN. The recommendation from this study is to include all BLU accounts in the Treasury Single Account (TSA) system.